2011
DOI: 10.1128/iai.01012-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Putative Chaperone Involved in Stress Resistance and Virulence in Francisella tularensis

Abstract: Francisella tularensis is a highly infectious bacterium causing the zoonotic disease tularemia. This facultative intracellular bacterium replicates in vivo mainly inside macrophages and therefore has developed strategies to resist this stressful environment. Here, we identified a novel genetic locus that is important for stress resistance and intracellular survival of F. tularensis. In silico and transcriptional analyses suggest that this locus (genes FTL_0200 to FTL_0209 in the live vaccine strain [LVS]) cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 36 publications
2
43
1
Order By: Relevance
“…Although we observed differences in the levels of intracellular replication between these two cell lines, the inFTS_1680 mutant showed significantly reduced replication in both cell lines, implying its importance for optimal intracellular replication. Phenotypic differences in intracellular proliferation within differing phagocytic cell lines have been observed with other attenuated Francisella mutants, as previously reported (5,6,34).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Although we observed differences in the levels of intracellular replication between these two cell lines, the inFTS_1680 mutant showed significantly reduced replication in both cell lines, implying its importance for optimal intracellular replication. Phenotypic differences in intracellular proliferation within differing phagocytic cell lines have been observed with other attenuated Francisella mutants, as previously reported (5,6,34).…”
Section: Discussionsupporting
confidence: 62%
“…3A). In contrast to our studies with inFTS_0201, it has previously been reported that intraperitoneal infection of BALB/c mice with a disrupted FTL_0205 gene (FTS_0201 ortholog) in the F. tularensis LVS strain revealed a strong attenuation (6). A possible explanation for the discrepancy in the reported virulence between the inFTS_0201 and inFTL_0205 mutant strains could be the variable number of NKD repeats existing in these orthologs, the clear differences in the challenge model, or simply that within the FSC200 strain other virulence factors mitigate the effect of FTS_0201 disruption, similarly to data published by Meibom et al (35).…”
Section: Fig 10contrasting
confidence: 53%
See 2 more Smart Citations
“…We have also demonstrated that the sodBC mutant of F. tularensis LVS, which carries a point mutation in the sodB gene and a clean in-frame deletion of the sodC gene, exhibits enhanced sensitivity toward ROS and RNS, attenuated survival in macrophages, and virulence in mice (30). In addition to these primary antioxidant enzymes, a moxR family ATPase encoded by the FTL_0200 gene and two additional genes present on the moxR locus of F. tularensis LVS are required for resistance against oxidative and pH stresses (31). Additionally, the ohr gene of F. novicida and F. tularensis LVS is required for resistance to organic hydroperoxides (32).…”
mentioning
confidence: 99%